The Influence of Convenience and Security on Purchasing Decisions: (A Case Study of BRImo QRIS Users in Pekalogan City) - Dwi Armiyati (Brilliant International Journal Of Management And Tourism, 2026)
Technological developments, especially in developing financial technology, can be related to user decisions. This research aims to determine whether convenience and security have a positive and significant influence on usage decisions, both partially and simultaneously. Case studies were conducted on BRI customers in Pekalongan City. The information collection procedure in this inquire about employments a survey within the frame of a Google frame. From the whole investigate populace, 50 individuals were moreover tested employing a purposive inspecting procedure concurring to the criteria decided by the analyst. The instrument tests utilized are legitimacy tests, unwavering quality tests and classical presumption tests. The hypotheses uses multiple linear regression analysis, t test and F test. The inquire about comes about concluded that comfort had a positive and critical impact on the choice to utilize QRIS BRImo in part, security had a positive and critical impact on the choice to utilize QRIS BRImo somewhat, comfort and security had a positive and critical impact on the choice to utilize QRIS BRImo at the same time (together).